The Mediterranean in Music: Critical Perspectives, Common Concerns, Cultural Differences - Cooper, David; Dawe, Kevin (Maryland The Scarecrow, 2005)
Politically and historically, the Mediterranean has been a space for critical dialogue for competing and often antagonistic voices, and still functions as meeting place for diverse and interdisciplinary approaches. Although other academic disciplines have attempted a unified approach to Mediterranean studies, until recently Mediterranean music as a singular concept has received relatively little scholarly development. This volume is a crucial first step and investigates several musical cultures that have traditionally demonstrated common threads, trends, and interactions. The music of Greece, Crete, Turkey, Albania, Corsica, Italy, Spain, Morocco, Algeria and Palestine are all considered in this volume as the scholars represented here reveal the musical commonality among otherwise divergent traditions. Unnecessary technical jargon is avoided, and an interdisciplinary approach embracing ethnology and material culture considerations makes this volume relevant not only to musicologists and anthropologists, but likewise to the general reader interested in tourism.
Keywords: Ethnomusicology; Music criticism